Bright persistent green emitting water-dispersible Zn2GeO4:Mn nanorods. Issue 22 (8th April 2020) - Srivastava, Bhupendra B.; Gupta, Santosh K.; Li, Yang; Mao, Yuanbing
Abstract : This work reports on a green and facile approach for designing bright and persistent green luminescent Zn2 GeO4 :Mn 2+ nano crystals with high quantum yield (∼52%) and water dispersibility designated for LEDs, security, and bio imaging. Abstract : Luminescent materials with bright and persistent emission have been attracting significant attention from the scientific community owing to their tremendous potential in the area of bioimaging, solid state lighting, and security applications. Moreover, when they are in a nanodomain and are water dispersible, their potential for in vivo and in vitro imaging is further increased. Keeping this in mind, we have synthesized water dispersible nanorods (NRs) of Zn2 GeO4 (ZGO) and Mn 2+ -doped Zn2 GeO4 (ZGOM) using the hydrothermal method. For the ZGOM NRs, we have also optimized the dopant Mn 2+ concentration, the pH value of the reaction medium, and the precursor Zn/Ge molar ratio. The ZGO NRs emit a bright bluish white (cool-white) emission under UV irradiation which is ascribed to the various kinds of defects present in NRs. On the other hand, the ZGOM NRs display a highly bright green luminescence under UV irradiation with a quantum yield (QY) of 52%. The best emission output was observed with a dopant concentration of 2.0 mol% Mn 2+, pH of 10.5, and Zn : Ge = 1 : 2. This fact suggests that zinc deficiency and excess of germanium lead to enhancement in emission intensity. More importantly, the undoped ZGO NRs could not display any kind of persistent luminescence, whereas the ZGOM NRs show excellent green afterglow properties (even visible with the naked eye) upon irradiation with 254 nm UV light. Such water dispersible nanocrystals with high QY and afterglow properties offer great potential for developing cost-effective and environmentally benign phosphors for multifunctional applications in society.